Extracorporeal shock wave treatment of capsular fibrosis after mammary augmentation – Preliminary results. (December 2013) - Heine, Norbert; Prantl, Lukas; Eisenmann-Klein, Marita
Abstract: Extracorporeal shock wave therapy has undergone continuous development and has become a well-established therapy option both in urology and in orthopaedics/trauma surgery. Experimental and clinical studies have proved the effectiveness of extracorporeal shock wave therapy in the treatment of connective tissue diseases such as fibromatosis. The pathomechanism of capsular fibrosis after augmentation of the female breast with silicone implants presents a series of analogies with mechanisms that are generally recognised to be associated with fibroproliferative diseases. The starting point of the disease is the inflammatory reaction caused by the silicone and/or by the sub-clinical bacterial contamination of the implant surface and can create an inflammatory reaction and fibrosis. A total of 19 cases of capsular fibrosis in 12 patients following insertion of mammary implants were treated with extracorporeal shock wave therapy. The therapy was performed with the Duolith SD1 system manufactured by Storz Medical. Shock waves were applied with the C-Actor handpiece designed for planar shock waves. Extracorporeal shock wave therapy appears to be a non-invasive, well-tolerated and easy-to-use procedure for pain reduction and fibrotic tissue softening, especially after aesthetic breast implant augmentation.